PERSEPSI PENDENGAR TERHADAP PROGRAM RADIO ( Studi Deskriptif Kualitatif Persepsi Pendengar Terhadap Program Buletin Lintas Pagi LPP RRI Surakarta Periode Juni 2014) - MAHAPUTRA, Dedy Chandra (2016)
The mass media are entitled to take part in the information industry, electronic media such as television and the Internet, for example, but especially radio also do the same thing, although the actual radio becomes secondary media because of competition from television and the Internet. But radio has what no other media owned, the radio is able to influence the listener's imagination, and a radio receiver inexpensive program, in addition to cheap radio is also easy to carry, as the present most phones already have a radio application. This study intends to find out how big the audience participation to the program of events on offer RRI. The method in this research is done using data triangulation technique. The technique of collecting information from sources that can provide information and meet the criteria set by the researchers. Results researchers found that the Bulletin Cross program is a flagship event LPP morning PRO 1 RRI Surakarta, as evidenced by the many interests of listeners from all walks of life. Program cross bulletin this morning to enter the broadcast reach very rural areas become a favorite of listeners. For the RRI are in response to a shortage of outstanding issues, whether it is true or false, so that people become aware of where kebenarnnya a news and cases that exist in the absence of environmental interactive phone when the event took place. So it becomes a bit limited audience participation.